2014
DOI: 10.2139/ssrn.2495074
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy, Financial Conditions, and Financial Stability

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 97 publications
(64 reference statements)
5
115
0
1
Order By: Relevance
“…This supports the view that accommodative monetary policy may contribute to a build-up of financial vulnerabilities, i.e. it may boost the credit cycle (Adrian and Liang, 2014). 36 The policy combinations in Table 3 should be regarded as dominant, but not always optimal and attainable.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This supports the view that accommodative monetary policy may contribute to a build-up of financial vulnerabilities, i.e. it may boost the credit cycle (Adrian and Liang, 2014). 36 The policy combinations in Table 3 should be regarded as dominant, but not always optimal and attainable.…”
Section: Discussionsupporting
confidence: 56%
“…The transmission of monetary policy through the credit channel is widely explored in the literature. It is generally accepted that easier monetary policy leads to an expansion of credit, as lower interest rates encourage borrowing (Adrian and Liang, 2014;Peek and Rosengren, 2013). 24 For example, Angeloni et al (2003) provide evidence for the credit channel in some of the largest euro area countries during 1993-1999.…”
Section: Transmission Of Cnb and Ecb Monetary Policy To Banks' Capitamentioning
confidence: 99%
See 1 more Smart Citation
“…While this paper does not address whether low interest rates lead to unhealthy reach for yield by banks, this has been a concern among many supervisors and policy makers, and has been a subject of research (see Adrian andLiang, 2014, andDell'Ariccia andMarquez, 2013, for literature reviews of the links between interest rates and risk taking). The negative consequences of low (for long) rates on bank profitability and capitalization are additionally important to consider as analysis has suggested that the incentives for (excessive) risk-taking depend not just on the level of interest rate but also on the capitalization and franchise value of the bank (Dell'Ariccia, Laeven and Marquez, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 Adrian and Liang (2016) call for a broader approach than just looking at credit when conducting cost-benefit analysis of LAW policy. Svensson (2017) also notes that an analysis of the benefits of LAW based on the impact of montary policy on credit has limitations, including limitations due to a moderate effect of monetary policy on real credit and credit to GDP.…”
Section: Introductionmentioning
confidence: 99%